Childhood Maltreatment, Low Serum Cortisol Levels, and Non-Suicidal Self-Injury in Young Adults With Major Depressive Disorders - Peng, Bo; Li, Jinmeng; Liu, Haitao; Fang, Han; Zhao, Weitan; Chen, Guanjie; Xiu, Meihong; Zhang, Yingli (Frontiers in Pediatrics, 2022)
Background: Non-suicidal self-injury (NSSI) is a serious public health problem widely present among young adults and adolescents. While, finding risk factors associated with NSSI among young patients with major depressive disorder (MDD) is challenging. The current study aims to measure the childhood adversity and serum cortisol levels and to elucidate their relationship in MDD patients with NSSI. Methods: In this cross-sectional study, 126 young patients with MDD (aged 16 to 35 years) were recruited. The depressive symptoms were assessed by the Beck Depression Inventory (BDI-II) and the childhood adversity was evaluated by the Chinese version of Childhood Trauma Questionnaire (CTQ) scale. Serum cortisol levels were determined by the kits in patients. Results: Relative to MDD patients without NSSI, MDD patients with NSSI had a higher CTQ total score and its four subscores. Moreover, the cortisol levels in MDD/NSSI patients were significantly decreased than in MDD patients without NSSI. For MDD/NSSI patients, there is a negative association between the cortisol levels and emotional neglect, but not for MDD patients without NSSI. Further regression analysis showed that low cortisol levels, BDI-II and emotional neglect were risk factors for NSSI in young MDD patients. Conclusion: Our findings suggest that young MDD patients with NSSI experience more childhood adversity and have lower cortisol levels. Also, lower cortisol levels were associated with childhood adversity but not with the depressive symptoms. Further, lower cortisol levels, depressive symptoms and emotional neglect were risk factors for NSSI in young MDD patients.